Digital Marketing Influence Research in Consumer Behavior : A Systematic Literature Review Using TCCM and Future Research Agenda - Pappu, Sindhuja; Kotni, V. V. Devi Prasad; Prasanna, Iragavarapu Lakshmi; Krishna, S. V. S. S. P. Jaya Sankar (Indian Journal of Marketing, 2025)
Purpose : The study aimed to explore how digital marketing influences consumer behavior through a systematic literature review using the theory context characteristics methods (TCCM) framework. The purpose was to identify key factors, gaps, and trends in the literature while offering suggestions for future research. Design/Methodology/Approach : The PRISMA model was used to identify, screen, make eligible, and include suitable documents for the study. A total of 112 papers were identified for this systematic literature review, which was performed using the TCCM framework. Findings : The most widely used theories were the technology acceptance model, attribution theory, cognitive development theory, theory of planned behavior, and theory of reasoned action. Various frequent contexts were found to be branding, e-WOM, repurchase intention, etc. The characteristics were websites, social media, search engines, digital platforms, etc. The various methods were SEM, DEMATEL, online reviews, etc. Research Implications : The study offered a holistic overview of the literature on consumer behavior influenced by digital marketing and tracing the evolution of digital marketing research in this domain. The study was able to provide future research directions in the domain. Practical Implications : The study highlighted how important it is for digital marketing components, more precisely, attributes, to impact consumer perceptions of products and businesses positively. To prevent impulsive purchases, practitioners should ensure that all the information they use in their marketing, advertising, and promotional strategies is provided. Originality/Value : This is one of the foremost studies that explored theories, contexts, characteristics, and methods related to digital marketing’s influence on consumer behavior using the TCCM method, which is very useful for the digital marketing industry.